2013
DOI: 10.1109/tgrs.2012.2225627
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of the First Measurements of Tropospheric Water Vapor and Temperature by the HAMSTRAD Radiometer Over Concordia Station, Antarctica

Abstract: International audienceThe HAMSTRAD microwave instrument operates at 60 and 183 GHz and measures temperature and water vapor, respectively, from 0- to 10-km altitude with a time resolution of 7 min. The radiometer has been successfully deployed at Dome C (Concordia Station), Antarctica (75°06' S, 123°21' E, 3233 m amsl) during the first summertime campaign for 12 days in January-February 2009. The radiometer has been continuously running since January 2010, hosted within a dedicated shelter. We have used the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 38 publications
2
41
0
7
Order By: Relevance
“…In the present study, the vertical profiles of temperature and humidity were taken from RS92 radiosondes using the standard Vaisala evaluation routines without any correction of sensor heating or time lag effect. We recall that the corrections performed on the radiosonde data measured in 2009 according to Miloshevish et al (2006) shown a weak impact (with a maximum of +4 % on IWV) on the vertical profiles (Ricaud et al, 2013). Furthermore, considering the updated tools developed in Miloshevich et al (2009) and Tomasi et al (2011Tomasi et al ( , 2012 found that, between 630 and 470 hPa, the correction factor for humidity estimated by the radiosonde varied within 1.10-1.15 for daytime and within 0.98-1.00 for night-time.…”
Section: Radiosondesmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, the vertical profiles of temperature and humidity were taken from RS92 radiosondes using the standard Vaisala evaluation routines without any correction of sensor heating or time lag effect. We recall that the corrections performed on the radiosonde data measured in 2009 according to Miloshevish et al (2006) shown a weak impact (with a maximum of +4 % on IWV) on the vertical profiles (Ricaud et al, 2013). Furthermore, considering the updated tools developed in Miloshevich et al (2009) and Tomasi et al (2011Tomasi et al ( , 2012 found that, between 630 and 470 hPa, the correction factor for humidity estimated by the radiosonde varied within 1.10-1.15 for daytime and within 0.98-1.00 for night-time.…”
Section: Radiosondesmentioning
confidence: 91%
“…It has been running automatically since January 2010. Science and validation studies using HAMSTRAD data are detailed in Ricaud et al (2012Ricaud et al ( , 2013Ricaud et al ( , 2014aRicaud et al ( -c, 2015. All the HAM-STRAD data measured since 2009 are freely available at the following address: http://www.cnrm.meteo.fr/spip.php?…”
Section: The Hamstrad Radiometermentioning
confidence: 99%
“…Once these tunings provide a calibrated spectrum with reduced undulations, vertical profiles will be obtained using the analysis tool Microwave ODIN Line Estimation and Retrieval (MOLIERE) originally developed for the space mission ODIN (Urban et al, 2003). It is based on the Optimal Estimation Method (Rodgers, 2000) to retrieve vertical profiles and has been successfully adapted to the ground-based H 2 O instruments: (1) MobRa, stratospheric H 2 O measured at 22 GHz , and (2) HAMSTRAD, tropospheric H 2 O measured at 183 GHz (Ricaud et al, 2013). Theoretical calculations (Motte, 2008) show that the DODO radiometer will be able to measure vertical profiles of H 2 O from ∼ 15 to ∼ 75 km with a resolution of 7-12 km.…”
Section: Passive Remote Sensing Measurementsmentioning
confidence: 99%
“…La précision sur les profils verticaux de H 2 O et de température du radiomètre Hamstrad pour un temps d'intégration de 7 minutes est présentée respectivement dans les tableaux 3 et 4, associée aux résolutions verticales dans la couche limite atmosphérique, la troposphère libre et la haute troposphère-basse stratosphère. Nous avons appliqué en parallèle la théorie de l'estimation optimale (Rodgers, 2000) aux mesures du radiomètre Hamstrad pour caractériser les résolutions verticales des profils de H 2 O et de température (Ricaud et al, 2013a). Les fonctions de balayage associées (ou noyaux moyens) permettent de caractériser la résolution verticale des mesures en calculant leur largeur à mi-hauteur.…”
Section: Le Programme Hamstradunclassified
“…Fonctions de balayage ou noyaux moyens de la température relatives aux mesures du radiomètre Hamstrad au Dôme C : à gauche de 3,2 à 4,2 km d'altitude (0-1 km au-dessus de la surface) ; à droite de 3,2 à 13,2 km d'altitude (0-10 km au-dessus de la surface). Les chiffres à droite de chaque graphe montrent, pour chaque fonction de balayage, 1) l'altitude du pic et 2) la résolution verticale estimée à partir de la largeur à mi-hauteur de la fonction de balayage (tiré de Ricaud et al, 2013a). de balayer à la fois l'absorbant à température ambiante (charge chaude pour l'étalonnage) et l'atmosphère à différentes élévations.…”
Section: Le Programme Hamstradunclassified